Environmental Biotechnology : a biosystems approach - Vallero, Daniel (San Diego : Elsevier Science & Technology Books, 2010)
Annotation For more than a century, biotechnology has acted as a vital buffer between people, pollution and the environment. The field is designed to moderate, if not eliminate, the stresses we inflict upon the world's ecosystems. In order to do this effectively, a systems approach must be employed to maximize the sustainability of our efforts and improve the long term health our environment.This book will address the questions of how and why knowledge and understanding of the physical, chemical, and biological principles of the environment must be achieved for the effective development of biotechnology applications. Using a systems biology approach, Environmental Biotechnology will provide a context for researchers and practitioners in environmental science. It will serve as a complement to the useful guidebooks which provide the necessary specifications and criteria for a wide range of environmental designs and applications by providing the underlying principles for the specifications, an area which is most important to scientific researchers in this arena to develop further technologies.* Provides a systems approach to biotechnologies which includes the physical, biological, and chemical processes in context* Case studies include cutting-edge technologies such as nanobiotechnologies and green engineering* Addresses both the applications and implications of biotechnologies by following the life-cycle of a variety of established and developing biotechnologies
Scholarly & Professional
Keywords: Environmental Biotechnology